2011
DOI: 10.1002/meet.2011.14504801085
|View full text |Cite
|
Sign up to set email alerts
|

The role of information avoidance in everyday-life information behaviors

Abstract: This paper presents the results from a study of information behaviors in the context of people's everyday lives as part of a larger study of information behaviors (IB). 34 participants from across 6 countries maintained a daily information journal or diary -mainly through a secure web log -for two weeks, to an aggregate of 468 participant days over five months. The textrich diary data was analyzed using Grounded Theory analysis. The findings indicate that information avoidance is a common phenomenon in everyda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 19 publications
2
67
0
Order By: Relevance
“…The results presented in Table 1 also provide support for the claim that information avoidance and information seeking are related but might be conceptually distinct (Case et al 2005;Kahlor et al 2006;Narayan, Case, and Edwards 2011). The behavioral indicator of information seeking behavior was not related to attitudes toward red meat and had different relationships with information processing, being positively related to systematic processing and negatively to heuristic processing.…”
Section: Journal Of Risk Researchsupporting
confidence: 59%
See 3 more Smart Citations
“…The results presented in Table 1 also provide support for the claim that information avoidance and information seeking are related but might be conceptually distinct (Case et al 2005;Kahlor et al 2006;Narayan, Case, and Edwards 2011). The behavioral indicator of information seeking behavior was not related to attitudes toward red meat and had different relationships with information processing, being positively related to systematic processing and negatively to heuristic processing.…”
Section: Journal Of Risk Researchsupporting
confidence: 59%
“…Several researchers have stressed that seeking and avoiding are related but conceptually distinct, and that it is necessary to understand each concept in its own right (e.g. Case et al 2005;Kahlor et al 2006;Narayan, Case, and Edwards 2011). For instance, screening the news to avoid reading about the risks of red meat (information avoidance) is quite different from not engaging in an online search for more information on the risks of red meat (the absence of information seeking).…”
Section: Information Avoidance and Cognitive Dissonance Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that individuals seek information that is in line with their current worldview and avoid information that may cause unpleasant feelings or thoughts (Gaspar et al, 2015;Narayan, Case, & Edwards, 2011). In an experimental study, Van Dijk, Fischer, De Jonge, Rowe, & Frewer (2012) found that, following information provision, positive initial attitudes were associated with lower levels of risk perception and higher levels of benefit perception.…”
Section: Initial Attitudementioning
confidence: 99%